Contesting Indonesia: Islamist, separatist, and communal violence since 1945 - Schulze, Kirsten E. (Cornell modern Indonesia project, 2024)
Contesting Indonesia explains Islamist, separatist and communal violence across Indonesian history since 1945. In a sweeping argument that connects endemic violence to a national narrative, Kirsten E. Schulze finds that the outbreak of violence is related to competing local notions of the national imaginary as well as contentious belonging.Through detailed examination of six case studies: the Darul Islam rebellions, Jemaah Islamiyah's jihad, and the conflicts in East Timor, Aceh, Poso, and Ambon, Schulze argues that violence was more likely to occur in places that are on the geographic, ideological, ethnic, and religious periphery of the Indonesian state; that violence by non-state actors was most protracted in locations where there was a well-established alternative national imaginary supported by an alternative historical narrative; and that violence by the state was most likely in places where the state had a significant territorial interest. Drawing on a vast collection of interviews and archival and published sources, Contesting Indonesia provides a new understanding of the history of violence across the Indonesian archipelago.